Kualitas Pelayanan Publik Pada Komunitas Adat: Studi Kasus Komunitas Orang Lom di Kabupaten Bangka Tahun 2012-2013 - Ristian, Andre; Suranto, Suranto (Universitas Muhammadiyah Yogyakarta, 2014)
The purpose of this study was to describe the quality of public services in the Air Abik dan Pejam, Gunung Muda in2012-2013. While the service quality measurement instrument in this study using Zeithaml thinking that; direct evi-dence / keterwujudan (tangible), responsiveness (responsiveness), reliability (Reliability), assurance (assurance)and empathy (empathy). Accompanied programs, practices and factors of quality of health care in the hamlet Air Abikand closed. The method used is the method mix (mix method). The results of the study indicate that the quality ofhealth services provided by Polindes and Pustu to Komunitas Adar Terpencil (KAT) People in Dusun Air Abik dan Pejam,Desa Gunung Muda and closed is good with 3:50 cumulative index value of a maximum value of 5. The dimensions ofempathy into the dimension with the highest value ie 4:10 and indicators assurance to a low of 2:30. tangible scored3.73, responsiveness got 3.78 and reliability with a value of 3.62. The service practices are in accordance SOP, andthe health care program is still equated with the program in the district. Is a factor that affects the law of customary/local knowledge, infrastructure, location and quality of the resource geogerafis aparatur. Conclusion of this researchis that the quality of health services provided by Polindes and Pustu on KAT People Lom in Hamlet Air Abik and closedeither with the index value 3.50 of the maximum value. The practice of health care provided was appropriate SOPexisting health services. The recommendation is that the government should pay more attention Bangka khsusunyahealth care quality improvement and infrastructure facilities.